Analyzing the Effect of Human Resource Competence and Incentives on Employee Performance: A Case Study at Sincera Clinic Palembang - Nadhilah, Faiza Putri; Heriyanto, Heriyanto; Trisninawati, Trisninawati (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose: This study analyzes the impact of human resource competence and incentives on employee performance at Sincera Clinic Palembang, aiming to enhance service quality and customer satisfaction. Methodology: A quantitative approach was used, with a structured questionnaire distributed to 28 employees and analyzed using SPSS, regression analysis, and hypothesis testing to explore the relationship between competence, incentives, and performance. Results: A strong correlation (R = 0.657) was found between competence, incentives, and employee performance. The adjusted R-squared value of 0.386 shows that 38.6% of performance variation is explained by these factors. Competence significantly impacts performance (t = 2.706, p < 0.05), while incentives do not (t = 1.476, p > 0.05). Findings: Competence has a more significant impact on employee performance than incentives, suggesting that improving employee skills and knowledge drives better outcomes. Novelty: This study provides new insights into the factors affecting employee performance in the beauty clinic industry, a sector with limited research in human resource management. Originality: The research focuses on the beauty clinic sector, offering empirical evidence of how competence and incentives influence employee performance in this niche market. Conclusions: Competence is crucial for improving employee performance, while incentives have less impact. Focusing on competence development is recommended. Type of Paper: Case Study research paper.